KOMPETENSI KEPRIBADIAN GURU DALAM PERSFEKTIF ISLAM - Lubis, Rahmat Rifai (Tazkiya: Jurnal Pendidikan Islam, 2016)
Nasih 'Ulwan try to provide specific criteria for becoming a teacher. Not only the science skills that must be mastered, but ownership of the mature personality is also a factor supporting the success of learning. even very large impact to be obtained by the students, when the teacher does not have the personality stretcher. According to personal competence as a medium for delivering the knowledge possessed by the teacher to the students. Keywords: Competence, Personality, Teacher.